A6.38 Toll-like receptor 7 and 9 in the pathogenesis of inflammatory autoimmune arthritis. (13th February 2015) - Fischer, A; Herman, S; Böhm, C; Saferding, V; Goncalves-Alves, E; Steiner, G
Abstract : Background and objectives: There is evidence that release and insufficient removal of endogenous nucleic acids may be involved in triggering harmful autoimmune reactions important in the initiation of systemic autoimmune diseases including rheumatoid arthritis (RA). Nucleic acid sensing molecules, such as the endosomal Toll-like receptors (TLRs) 7 and 9, have been linked to pathogenetic autoimmune processes, particularly in systemic lupus erythematosus, but their role in RA is less clear. We aimed to study the role of TLR7 and TLR9 in the pathogenesis of inflammatory arthritis by antagonising or stimulating them in rats with pristane-induced arthritis (PIA). Materials and methods: Arthritis was induced in Dark Agouti rats with the mineral oil pristane. Antagonists or agonists, respectively, for TLR7 and TLR9, a non-inhibitory control sequence or PBS as placebo were applied every other day. Treatment was started before disease induction. Arthritis was scored using established scoring systems, inflammation and bone erosion were quantified by histological analysis. Serum cytokine levels were measured by ELISA. Results: While the control sequence showed no effect on arthritis development and severity, the TLR9 antagonist reduced arthritis severity significantly in PIA. In contrast, a slight aggravation of disease severity was observed in animals treated with the TLR7 antagonist. Inhibition of TLR9 led to strongly reduced bone erosion, whereas it appeared moderately aggravated in animals treated with the TLR7 inhibitor. Furthermore, IL-6 serum levels were reduced in animals treated with the TLR9 antagonist. However, these effects were only seen when the inhibitor was applied before disease onset. When treatment with the antagonists was started at disease-onset neither disease severity nor bone erosion were affected. Treatment with agonists for TLR9 or TLR7 showed no significant effect on disease severity in animals treated with the TLR9 agonist. In contrast, disease was significantly aggravated in animals treated with the TLR7 agonist and this effect was more pronounced than that observed in previous experiments with the TLR7 antagonist. Conclusions: Inhibition of TLR9 in rats with PIA significantly reduced inflammation and bone erosion whereas stimulation of TLR7 aggravated disease severity. Therefore, these results suggest different roles for TLR7 and TLR9 in the T cell-dependent initiation phase of PIA and thus an important involvement of the DNA (CpG) recognising TLR9 and the RNA recognising TLR7 in the initiation of autoimmune arthritis which needs to be further elucidated in ongoing and future experiments.